DETEKSI RISIKO SISTEMIK DAN KETERKAITAN KEUANGAN: STUDI PADA INSTITUSI KEUANGAN DI INDONESIA - Rihana Sofie Nabella; Setyo Tri Wahyudi; Dewani Indah Tawakalni (Department of Management, Faculty of Economics, Universitas Islam Sutan Agung, Semarang, 2020)
The purpose of this study is to measure systemic risk and financial linkages in financial institutions in Indonesia. The financial sector plays a vital role in the economy. On the other hand, this sector is also vulnerable to crises or risks, one of which is systemic risk. This study uses a sample 20 financial institutions from January 2012 to December 2018 with the Conditional Value at Risk (CoVaR) model. The results obtained show that the size of an institution does not determine the amount of systemic risk contribution. Based on the average systemic risk contribution obtained that insurance companies become the largest contributor to systemic risk.